Cuando la conservación no puede seguir el ritmo del desarrollo: Estado de salud de los ecosistemas coralinos del Pacífico Norte de Costa Rica - Alvarado, Juan José (2018)
Abstract: When conservation can keep up with development´s pace: Health status of coral ecosystems in the North Pacific of Costa Rica. Coral reefs are diverse and productive ecosystems, despite this, they are being threatened by human activities that enhance the detrimental impact of the natural phenomenon’s like Harmful Algal Blooms (HAB). The north Pacific of Costa Rica has been characterized as one of the best regions for the coral reefs development in the country. However, many of these ecosystems are being lost as a result of eutrophication, overfishing, invasive species and others impacts that affect the region. In the present study, live coral cover in the north Pacific was 5.0 ± 10.4(s.d.) %, with a domination in the ecosystems by turf algae. Twenty-six invertebrate taxa were registered in the region with the predominance of the sea urchin Diadema mexicanum. Ninety-four species of reef fish were identified. Snappers and some planktivores species were the groups with the highest frequency and abundance. The localities previously studied in the 1990 decade, presented a mean live coral cover between 40-50 %, whereby the actual state of the reef reflect a significant deterioration. This decline in coral cover is due to natural events like the El Niño, as well as the decrease in water quality in the region. In recent years, proliferations of the invasive seaweed Caulerpa sertularioides and high densities of bioerosive sea urchins have been reported, mainly associated with HAB events. Likewise, fish communities have low biomass, especially in the vicinity of fishing villages. The state of the reefs in the North Pacific is worrying and requires actions for its recovery and conservation, for which there must be better planning of the development of projects and activities on the coast. Rev. Biol. Trop. 66(Suppl. 1): S280-S308. Epub 2018 April 01.